Immunoreactive atrial natriuretic peptide and autoradiographic distribution of atrial natriuretic peptide binding sites in the brain of the antarctic fish, Chionodraco hamatus - PESTARINO, MARIO; CANDIANI, SIMONA; MASINI, MARIA ANGELA; M. STURLA; A. AUGELLO; D. OLIVERI; VALLARINO, MAURO (Polar Biology, 2000)
The anatomical distribution of atrial natriuretic peptide (ANP)-immunoreactive structures and the autoradiographic localization of ANP binding sites were studied in the brain of the Antarctic fish, Chionodraco hamatus. ANP-containing elements were colocated with ANP binding sites in the dorsal medial and lateral subdivisions of the telencephalon, prethalamic nuclear complex, and in the nucleus of the medial longitudinal fasciculus of the mesencephalon. However, mismatching was observed in other brain regions, particularly at mesencephalic and metencephalic levels. In the pituitary, ANP immunoreactivity occurred only in the pars dis- talis, whereas ANP binding sites were localized in the whole pituitary. In this paper we describe the occurrence of ANP immunoreactivity and ANP binding sites in the brain and pituitary of an Antarctic fish. In particular, in the cerebellum and pituitary of C. hamatus, ANP bind- ing sites are distributed in corresponding brain regions of dipnoans, amphibians and mammals. The immuno- cytochemical and histoautoradiographic data suggest that ANP acts as neuromodulator in the brain of C. hamatus. Moreover, the presence of ANP-like sub- stances in tanycytes lining the diencephalic ventricle suggests a chemosensorial role for such liquor-contact- ing cells and a possible modulatory effect of ANP on the osmoregulation of the cerebrospinal fluid.